Islamic Boarding School And The Implementation Of Diversity Value - Zayadi, Zayadi; Hafizallah, Yandi (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2023)
This article aims to explain the diversity in the concept of Islam in Bangka Island which consists of tolerance values, equality values, democracy values, and justice values. As for internalizing the value of diversity on Bangka Island, it includes four cultures, namely, religious culture, scientific culture, social culture, and political culture. Meanwhile, the pesantren's strategy in maintaining diversity is the absence of dichotomy in education, no ethnic and cultural exclusivity, teaching moderate understanding, instilling a sense of love for the motherland, and opportunities for women to develop intellectual power on an equal footing with men.